Organizing exhibitions a handbook for museums, libraries and archives - Matassa, Freda (London Facet Publishing, 2014)
This ground-breaking book is the first to provide librarian's, archivists and museum staff with practical guidance to creating and organizing successful exhibitions. Drawing on international museum practice but applicable to any exhibition or display, the book sets out a time-line from the initial idea to the final legacy. Backed up by advice and guidance and with a list of resources for those who need in-depth information such as international laws and standards applying to museum loans, it has up-to-date information on new developments such as flexibility in environmental conditions and sustainability and lists the top-ten tips for exhibition success and the ten biggest mistakes. Written by an international expert and designed for the first-time exhibition organizer as well as the professional and a key work for cultural management students, this book will become the standard for exhibition success. Readership: Librarians, archivists, museum staff, students of museum studies, cultural management and LIS and anyone who needs practical guidance on organizing exhibitions of any size.
Includes bibliographical references (pages 289-294) and index.
Keywords: Museum exhibits -- Planning; Museum techniques; Exhibitions